Influence of Online Learning Platforms Use on Foreign Students Language Education Proficiency and Cultural Competence - Laguador, Perfecta; Garbida, Yazel Iñin J; Garcia, Reighmonde B; Bucu, Carlene Briana; Guevarra, Seth Jofel; Ramos, Rowena Imelda A; Abcede, Blossom Dalyn D; Perdido, Jonathan A; Ibanez, Mercedes M (11th International Scholars Conference, 2024)
Having good communication skills and understanding other country’s language and their culture help foreigners adjust easily and enjoy their stay in other countries. Through the help of modern technology like the use of different online learning platforms, learning about the language and culture of other countries is much easier for the foreigners. Online learning platforms require students to have their own study schedule, download documents, learn, and analyze things by their own or other people that can help them. Thus, this study determined the influence of online learning platforms use on foreign students’ language education and cultural competence. Descriptive-correlational research design was applied and purposely included 54 foreign students to answer the research problem. Findings show that foreign students highly use online learning platforms. They also rated the level of their language education proficiency as average and high on cultural competence. The researchers found that online learning platforms use influence the language education proficiency and cultural competence of foreign students. Also, the use of online learning platforms predicts language education and cultural competence of foreign students. Moreover, this study concludes that teachers should encourage students to participate and use online learning platforms to boost their language education proficiency and cultural competence. Finally, teachers need to provide foreign students with lessons and activities that can incorporate to the use of online learning platforms.